2020
DOI: 10.1002/hed.26533
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs deregulation in head and neck squamous cell carcinoma

Abstract: Head and neck (HN) squamous cell carcinoma (SCC) is the eighth most common human cancer worldwide. Besides tobacco and alcohol consumption, genetic and epigenetic alterations play an important role in HNSCC occurrence and progression. microRNAs (miRNAs) are small noncoding RNAs that regulate cell cycle, proliferation, development, differentiation, and apoptosis by interfering in gene expression. Expression profiling of miRNAs showed that some miRNAs are upregulated or downregulated in tumor cells when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 221 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…A single miRNA might control a great number of RNA transcripts and contribute to various cellular signaling pathways under both normal and pathological conditions [ 10 , 12 ]. A vast number of studies have shown that aberrantly expressed miRNAs can function as oncogenes and/or tumor suppressors in human cancer cells, including HNSCC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single miRNA might control a great number of RNA transcripts and contribute to various cellular signaling pathways under both normal and pathological conditions [ 10 , 12 ]. A vast number of studies have shown that aberrantly expressed miRNAs can function as oncogenes and/or tumor suppressors in human cancer cells, including HNSCC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs was usually defined as oncogenes and suppressor genes in HNSCC. A recent study reviewed upregulated and downregulated miRNAs in HNSCC [ 32 ] and showed multiple well-studied miRNAs in HNSCC. Among them, hsa-miR-1, hsa-miR-31, hsa-miR-141, hsa-miR-146, hsa-miR-155, hsa-miR-200, hsa-miR-203, and hsa-miR-205 were commonly downregulated in the tumor necrosis group compared to those in the benign inflammatory necrosis group.…”
Section: Discussionmentioning
confidence: 99%
“…There have been significant advancements in surgery, radiotherapeutics, chemotherapy and immunotherapy as treatment approaches. In radiotherapy, the development of different fractionating schemes and intensity-modulated radiotherapy has enhanced the delivery and tolerance of radiation ( 32 ). Organ function conservation is improved through the advancement in conservative surgical procedures, including laryngeal prosthesis, laser surgery and hemilaryngectomy ( 33 ).…”
Section: Introductionmentioning
confidence: 99%